Predictors of readmission for postpartum preeclampsia - Rodney A. McLaren; Melissa Magenta; Laura Gilroy; Maria Gabriela Duarte; Sujatha Narayanamoorthy; Jeremy Weedon; Howard Minkoff (Taylor & Francis Group, 2021)
Objective: To develop a predictive model for re-admission for postpartum preeclampsia (PPEC). Methods: A case-control study; cases were patients re-admitted for PPEC; controls were not re-admitted. Mixed linear modelling was used to develop a predictive model on the training set, then validated on the validation set. Results: Two-hundred-sixty-nine patients were readmitted, and matched to 538 controls. A risk calculator was developed and yielded a sensitivity and specificity for readmission of 80.9% and 53.5%, respectively. Conclusion: A predictive model using age, race, discharge blood pressures, and preeclampsia was able to predict re-admission for PPEC with a high level of sensitivity.